Is seasonal net community production in the South Pacific Subtropical Gyre anomalously low?. Issue 18 (17th September 2016) - Bender, Michael L.; Jönsson, Bror
Abstract: The region of the South Pacific Subtropical Gyre (SPSG) at 20°–30°S, 140°–110°W is the oceanic area with the lowest chlorophyll concentration and the deepest nutricline, O2 saturation horizon, and euphotic zone. We analyze the limited available data from this region to determine if rates of net community production (NCP) are systematically lower than elsewhere. We present limited mixed layer O2 /Ar data constraining mixed layer NCP, examine hydrographic data from the CLIVAR repeat hydrography P18 line to assess seasonal dissolved inorganic carbon drawdown, and review results from the literature. While it is not possible to formalize uncertainties, the evidence suggests that euphotic zone NCP is around the lower end (~1 mol m −2  yr −1 ) of rates observed elsewhere. However, NCP is shifted to unusually deep depths, a change enabled by the very low extinction coefficients of these waters. Key Points: Net community production in the South Pacific is "normal" despite highly oligotrophic conditions Production in the South Pacific extends to unusually deep depths in the water column Sea surface irradiance appears to be an important control on NCP throughout the oceans